KAJIAN KARAKTERISTIK FISIK PUPUK GRANUL UREA-BIOCHAR BAMBU BERSELAPUT ASAM AKRILAT - Ni Nyoman Ari Putri Murtiyah; Ni Ketut Karina Sari; Dewa Ayu Ari Febriyanti; I Wayan Dirgayana (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
Nitrogen use efficiency in conventional urea fertilizers remains low due to nutrient loss through leaching and volatilization. This study aims to develop and characterize a slow-release fertilizer (SRF) based on a bamboo biochar matrix coated with acrylic acid polymer. The fertilizers were formulated into granules using coating and matrix methods with urea proportions of 25%, 30%, and 35%. Characterization included physical properties, surface morphology, and elemental composition using Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy (SEM-EDS). The results showed that the produced granules were dominated by sizes of 2–5 mm, ranging from 80.17% to 92.50%, complying with the Ministry of Agriculture Regulation (Permentan) No. 01 of 2019. SEM analysis confirmed that acrylic acid successfully encapsulated the pores of the bamboo biochar and urea, forming a physical barrier structure that extends the nutrient diffusion path. EDS spectra verified the successful impregnation of urea into the matrix, with Nitrogen (N) retention of 41.15% for the coating method and 27.97% for the matrix method. The presence of bamboo biochar micropores and the polymer layer aligns with slow-release principles, enhancing agronomic efficiency while minimizing environmental impacts.